Examining the performance of teacher graduates from Limpopo rural university - Thaba-Nkadimene, K.L.; Mmakola, S.D. (South African Journal of Higher Education, 2019)
Schools in Limpopo Province are facing learners’ underperformance, and a blame is levelled on poor teachers’ performance. Teacher Education Centres that train educators for the Limpopo Province are also blamed for training teachers who fail to deliver quality teaching and learning because of their lack of necessary teaching skills that are required to improve learners’ performance. The study aimed at examining the performance of teachers and how schools’ contextual factors impact on their teaching practice. The main research question that drove the study is ‘what are possible causes of poor performance of teachers in Limpopo rural schools?’ Critical Social Theory was used to understand the causes of poor performance of teachers, and the contextual factors that influence the teaching practice. Twelve teacher graduates from one rural Limpopo university were purposively sampled. The findings range from lack of teaching competencies; lack of school resources and infrastructure; and challenged home background. In conclusion, when teacher training has to be blamed for production of teachers who lack adequate teaching competencies, the Department of Education is blamed for not providing adequate school resources and infrastructure vital for the creation of conducive learning environment, and delivery of quality education and learning. This study recommends that improved working conditions in schools that enhances high levels of teachers’ performance should be made.